A Novel Therapeutic Approach to Improving Quality of Life and Performance in Athletes and Other Patients with Cluster Headache - Lewczuk, Michał; Trędota, Natalia; Czyżewicz, Zuzanna; Dworak, Kinga; Posid, Dominika; Dańda, Karol; Chludek, Aleksandra; Chobot, Barbara; Wachowska, Marta; Chmielowiec, Julia (Quality in Sport, 2026)
Background: Cluster headache is a severely disabling headache disorder. Despite the availability of acute and preventive therapies, treatment efficacy remains incomplete, leaving many athletes and other patients with insufficient symptom control leading to decreased quality of life and performance. Increasing interest has emerged in psychedelic compounds, particularly psilocybin, as potential therapeutic agents. Aim: This narrative review aimed to evaluate the current evidence regarding psilocybin in the treatment of cluster headache. Material and Methods: A literature search was conducted in the MEDLINE database to identify publications describing psilocybin use in cluster headache. Eight relevant publications were identified. Results: Clinical evidence remains limited but suggests potential therapeutic benefit. A randomized placebo-controlled trial demonstrated numerically higher response rates with psilocybin compared to placebo, although statistical significance was not achieved. An open-label study reported a mean reduction in attack frequency and identified changes in hypothalamic–diencephalic functional connectivity associated with clinical improvement. Observational studies consistently reported high patient-perceived efficacy for both abortive and preventive use, often exceeding satisfaction reported with conventional therapies. However, interpretation is limited by methodological constraints. Available data suggest a generally favorable safety profile, though psychological adverse effects may occur and long-term safety remains uncertain. Conclusions: Current evidence indicates a signal of therapeutic potential for psilocybin in cluster headache, particularly in preventive treatment, but remains insufficient for definitive clinical conclusions. Well-designed randomized controlled trials with standardized protocols are urgently needed to clarify efficacy, safety, and optimal therapeutic frameworks.